Mollusks from the upper Shackleton Limestone (Cambrian Series 2), Central Transantarctic Mountains, East Antarctica. (9th January 2019) - Claybourn, Thomas M.; Jacquet, Sarah M.; Skovsted, Christian B.; Topper, Timothy P.; Holmer, Lars E.; Brock, Glenn A.
Abstract: An assemblage of Cambrian Series 2, Stages 3–4, conchiferan mollusks from the Shackleton Limestone, Transantarctic Mountains, East Antarctica, is formally described and illustrated. The fauna includes one bivalve, one macromollusk, and 10 micromollusks, including the first description of the species Xinjispira simplex Zhou and Xiao, 1984 outside North China. The new fauna shows some similarity to previously described micromollusks from lower Cambrian glacial erratics from the Antarctic Peninsula. The fauna, mainly composed of steinkerns, is relatively low diversity, but the presence of diagnostic taxa, including helcionelloid Davidonia rostrata (Zhou and Xiao, 1984), bivalve Pojetaia runnegari Jell, 1980, cambroclavid Cambroclavus absonus Conway Morris in Bengtson et al., 1990, and bradoriid Spinospitella coronata Skovsted et al., 2006, as well as the botsfordiid brachiopod Schizopholis yorkensis (Ushatinskaya and Holmer in Gravestock et al., 2001), in the overlying Holyoake Formation correlates the succession to the Dailyatia odyssei Zone (Cambrian Stages 3–4) in South Australia.